The Role of Pitch and Timbre in Voice Gender Categorization - Pernet, Cyril R.; Belin, Pascal (Frontiers in Psychology, 2012)
Voice gender perception can be thought of as a mixture of low-level perceptual feature extraction and higher-level cognitive processes. Although it seems apparent that voice gender perception would rely on low-level pitch analysis, many lines of research suggest that this is not the case. Indeed, voice gender perception has been shown to rely on timbre perception and to be categorical, i.e. to depend on accessing a gender model or representation. Here, we used a unique combination of acoustic stimulus manipulation and mathematical modelling of human categorization performances to determine the relative contribution of pitch and timbre to this process. Contrary to the idea that voice gender perception relies on timber only, we demonstrate that voice gender categorization can be performed using pitch only but more importantly that pitch is used only when timber information is ambiguous (i.e. for more androgynous voices).